2020
DOI: 10.3389/fonc.2019.01524
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics Identifies 3-Hydroxyadipic Acid, d-Galactose, Lysophosphatidylcholine (P-16:0), and Tetradecenoyl-l-Carnitine as Potential Predictive Indicators of Gemcitabine Efficacy in Pancreatic Cancer Patients

Abstract: Gemcitabine (GEM)-based chemotherapy is the standard regimen for the treatment of pancreatic cancer (PC). However, chemoresistance is a major challenge in PC treatment. Reliable biomarkers are urgently needed to predict the response to GEM-based therapies. GEM-sensitive (GEM-S) and GEM-resistant (GEM-R) pancreatic carcinoma xenograft models were established, and GEM monotherapy and GEM plus nanoparticle albumin-bound paclitaxel (nab-PTX) doublet therapy were administered to GEM-S/R tumor-bearing mice. Metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…At present, the accurate detection of LPC relies on metabolomics or lipidomics technology, which provides assays for exploiting the role of LPC in chronic pain. Apart from chronic pain, LPC or LPC species in body fluids such as blood, urine, cerebrospinal fluid, and tissues are uniquely or collectively related to cancer [ 150 , 151 , 152 ], diabetes [ 153 , 154 , 155 , 156 ], coronary atherosclerosis [ 157 ], Alzheimer’s disease [ 158 , 159 ], rheumatoid arthritis [ 83 ], COVID-19 [ 160 ], liver and kidney damage [ 161 , 162 ], etc. Whether LPC is necessary for other chronic pain conditions, such as cancer pain, has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the accurate detection of LPC relies on metabolomics or lipidomics technology, which provides assays for exploiting the role of LPC in chronic pain. Apart from chronic pain, LPC or LPC species in body fluids such as blood, urine, cerebrospinal fluid, and tissues are uniquely or collectively related to cancer [ 150 , 151 , 152 ], diabetes [ 153 , 154 , 155 , 156 ], coronary atherosclerosis [ 157 ], Alzheimer’s disease [ 158 , 159 ], rheumatoid arthritis [ 83 ], COVID-19 [ 160 ], liver and kidney damage [ 161 , 162 ], etc. Whether LPC is necessary for other chronic pain conditions, such as cancer pain, has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Such information subsequently facilitates the discovery of biomarkers that are associated with pathologic conditions and play vital roles in mapping the effectiveness of drug therapies through various metabolomics approaches [141]. The identification of metabolic pathways affected by a specific drug treatment through metabolomics, as well as a subsequent analysis of genetic variations within these metabolic pathway components could help to achieve personalized medicine [138,142,143]. Profiling of drug-induced changes in metabolites or creating metabolite signatures of different disease subtypes, such as invasive or non-invasive tumors, through high-resolution targeted metabolomics tools serves an important biomarker discovery and diagnostic tool development [143][144][145].…”
Section: Pharmacometabolomicsmentioning
confidence: 99%
“…Wu et al adopted UPLC/Q-TOFMS for mapping the metabolic profiles following GEM monotherapy or combination therapy. They found that both monotherapy and combination therapy contribute to significant metabolic changes, and the relative levels of 3-hydroxyadipic acid, d-galactose, LysoPC (P-16:0), and tetradecenoyl-l-carnitine could be regarded as biomarkers to predict the efficacy of chemotherapy (58).…”
Section: Gemcitabinementioning
confidence: 99%